Estandarización de protocolos para el enriquecimiento y aislamiento de ADN Genómico de parásitos de los géneros Plasmodium, Haemoproteus, Leucocytozoon causantes de la malaria aviar en la amazonia peruana. - Galvez Zagaceta, Paula Alessandra (2022)
The study of malaria in birds in these last two decades has been increasing, for this, rapid and low-cost protocols are being developed for the extraction of genomic DNA, amplification and screening, allowing the presence of these hemoparasites to be detected. The objective of this research was to compare genomic DNA isolation protocols and to identify birds parasitized by the Plasmodium, Haemoproteus and Leucocytozoon genera that cause avian malaria in the Loreto Region, for which the salt precipitation protocol was used and modified ( Salting-out) and the method of isolation of blood cells by density gradient according to the conditions of the collected sample, proceeding to amplify by means of the Polymerase Chain Reaction in real time (qPCR) obtaining as results that the salt precipitation protocol showed better results in terms of its concentration and quality of ratios compared to the method of isolation of cells by density gradients, indicating that the DNA obtained does not present contaminants, being able to successfully carry out the identification of malaria avian by qPCR, identifying 170 parasitized birds where the Passeriforme order and the Thamnophilidae family are the groups with the highest numbers of infected birds. In conclusion, the standardized Salting out protocol is efficient for the detection of avian malaria, becoming a valuable tool in the field for the rapid detection and expansion of the investigation of these hemoparasites.